PEMANFAATAN BANTUAN PKH BAGI MASYARAKAT PENERIMA BANTUAN DI DESA SIDOREJO KABUPATEN SIDOARJO - Febrianti, Rr Diana (Paradigma, 2021)
Poverty is a condition of economic inability to meet the needs of the daily standard of living of the average community in an area. This condition of poverty is characterized by low daily income received to be allocated to basic daily needs. This study aims to identify poor families who are recipients of the Program Keluarga Harapan or PKH assistance in utilizing the assistance in Sidorejo Village, Sidoarjo Regency. Describe the allocation of aid funds, the dependence of beneficiaries on the assistance provided and explain the real and unanticipated functions in the utilization of the Program Keluarga Harapan assistance. The method used in this research is qualitative with a participant observation approach, namely the researcher is involved in the daily activities of the subject. The results showed that the aid had been distributed to underprivileged families. However, in terms of utilization, the lack of education caused problems to arise such as improper use of aid funds and also many parties trying to obtain unilateral benefits. This is a latent function found in this study. Keywords: Utilization, Program Keluarga Harapan, Function